EFFICIENCY ANALYSIS OF FINANCIAL PERFORMANCE COMPANY BEFORE AND AFTER THE ACQUISITION, MERGER. (Case study in 1994-2005 manufacturing company listed on the Jakarta Stock Exchange) - Ch. Benjamin, Verawaty; Supardi, MM, Drs. (Accounting, 2009)
Internal growth is the expansion done by building a business or new business unit from scratch (start-ups business). This path requires a different pertahapan ranging from market research, product design, recruitment of experts, market testing, procurement and construction of production facilities / operations before the company sold products to the market. Instead of external growth by buying existing companies. Mergers and Acquisitions is an external growth strategy and is a fast path to access a new market new products without having to build from scratch. There is a very significant time savings between internal and external growth through mergers and acquisition. The merger is an alternative for companies in order to expand its business, particularly the external expansion in order to increase the competitiveness of companies for corporate survival tesebut can be guaranteed. In a merger or acquisition, with the merger of two or more companies, it will strengthen the company´s ability to pay its short term debts. Hence in this study showed that companies doing mergers and acquisitions have a current performance ratio better than before the mergers and acquisitions. Companies that make mergers and acquisitions also have noneconomic motive to increase the company´s sales volume. In theory the existence of merger and acquisition transactions can increase sales. There are significant differences in the level of efficiency in the form of Debt to Equity Ratio (DER) at the company after the mergers and acquisitions. This is because after the merger and acquisition of the company´s financial structure improved, as shown by the lower use of debt in the venture capital firm. keyword:capital,company,acquicition